Development of Nanocellulose-Based Biomaterials from Agricultural Waste for Bone Tissue Regeneration Applications - Mei, Chen; Li, Zhang; Hui, Zhou (Yayasan Adra Karima Hubbi, 2024)
Agricultural waste has great potential to be used as biomaterial raw materials that can be used in medical applications, especially for bone tissue regeneration. Nanocellulose, which is produced from natural cellulose, offers good mechanical properties and high biocompatibility. This research aims to develop nanocellulose-based biomaterials from agricultural waste for bone regeneration applications. The purpose of this study is to explore the potential of agricultural waste, such as rice straw, peanut husks, and corn leaves, in producing high-quality nanocellulose that can be used for applications in the field of bone tissue regeneration. This study uses an experimental design with a laboratory approach. Agricultural waste is treated through nanocellulose extraction using certain chemical techniques. Material characterization was carried out using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR), as well as biocompatibility tests using osteoblast cell cultures. The results show that rice straw produces nanocellulose with the highest cellulose content (65%) and has optimal tensile strength and degradation time for bone tissue applications. Peanut husks and corn leaves also show good results, although not as good as rice straw. Agricultural waste, especially rice straw, has great potential to be used as a raw material for nanocellulose that can be used in bone tissue regeneration applications. This research opens up opportunities to develop more sustainable and affordable biomaterials for medical applications.